2014
DOI: 10.1121/1.4867365
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic detection, tracking, and characterization of three tornadoes

Abstract: Acoustic data recorded at 1000 samples per second by two sensor arrays located at ranges of 1-113 km from three tornadoes that occurred on 24 May 2011 in Oklahoma are analyzed. Accurate bearings to the tornadoes have been obtained using beamforming methods applied to the data at infrasonic frequencies. Beamforming was not viable at audio frequencies, but the data demonstrate the ability to detect significant changes in the shape of the estimated power spectral density in the band encompassing 10 Hz to approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…While, latent heat effects, radial vortex oscillations that include non-columnar nature of a tornado, and non-equilibrium effects are consistent with observations. In addition, it was noted that the current observations did not measure at sufficiently high frequency (> 100 Hz) to assess the aeroacoustic jet turbulence signature proposed in Frazier et al (2014).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…While, latent heat effects, radial vortex oscillations that include non-columnar nature of a tornado, and non-equilibrium effects are consistent with observations. In addition, it was noted that the current observations did not measure at sufficiently high frequency (> 100 Hz) to assess the aeroacoustic jet turbulence signature proposed in Frazier et al (2014).…”
Section: Discussionmentioning
confidence: 90%
“…While the current work does not aim to attribute the observations to a specific mechanism, it can be informative to compare the current observations to proposed mechanisms. First, it should be noted that the higher frequency signature Frazier et al (2014) observed and demonstrated to be consistent with aeroacoustic jet turbulence was not observed. This is expected since Frazier et al…”
Section: B Comparison With Potential Mechanismsmentioning
confidence: 94%
See 3 more Smart Citations